Peningkatan Literasi Informasi Melalui Program Pojok Baca Perpusnas Bagi Anak-Anak di Desa Teratak - Wahyu Astiko; Dimas Rizky Rahmatullah; Annisa Febrina Hidayat; Samara Kartika Cinta; Teguh Bachtiar; Khairul Walik; Dara Juliastina; Devi Septiani; Maryati; I Wayan Sumaha Artha Jaya; Gede Agung Subawa (Universitas Mataram, 2026)
The low level of information literacy among children in rural areas remains a significant challenge in achieving equitable educational development. In Teratak Village, although the village library has initiated several literacy activities, its function as an inclusive and sustainable information learning space has not yet been fully optimized. This program aimed to enhance children’s information literacy through the implementation of the Pojok Baca Perpusnas program in Teratak Village. The program was conducted using a participatory approach integrated into the Community Service Program (KKN), actively involving children, library managers, and community members. Activities included the establishment of a child-friendly reading corner, guided reading and discussion sessions, literacy visits to local schools, and mentoring to strengthen children’s abilities to access and understand information. Focus Group Discussions and continuous assistance were carried out to evaluate program implementation and ensure sustainability. The results indicate increased reading interest and active participation among children in literacy activities. The program also strengthened children’s basic skills in accessing, understanding, and communicating information obtained from reading materials. Overall, the Pojok Baca Perpusnas program contributed to reinforcing the role of the village library as a community learning center and fostering a sustainable literacy culture in Teratak Village.